AAR654: Building Services II / Faculty Of Architecture, Planning & Surveying - UiTM, Faculty of Architecture, Planning & Surveying (Universiti Teknologi MARA (UiTM), 2023)
A study of vertical and horizontal transportation systems, fire protection, mechanical ventilation and air conditioning systems. Emphasis will be on the principles and choices of system for different types and scale of buildings.